Fauna edáfica como bioindicador ambiental em áreas de Caatinga sob pastejo caprino - Santos, Marilania da Silva (2016)
This study was conducted to evaluate Soil fauna as environmental bioindicator in Caatinga areas under goat grazing in the Northeast Brazilian semi-arid. The experiment was conducted during one year (October 2013 to September 2014), at the Experimental Farm, belonging to the Federal University of Paraiba, located in Sao Joao do Cariri – PB - Brazil. We used three contiguous areas of Caatinga corresponding to the treatments: T1 (10 goats), T2 (5 goats) and T3 (No goats), each area had a size of 3.2ha with 30 sample units distributed. Were used male goats, adults without defined breed. To organisms soil macrofauna monthly collections was used to trap the type Provid, they remained in the area for 96 hours. Along with this collection was performed the soil mesofauna collection, consisting of soil and litter areas removed with a metal ring help. At the laboratory, the organisms were identified about order. To evaluate the orders diversity were used Shannon and Equitability indices at Past program. The abundance, wealth, absolute and relative frequency was calculated by Excel program. Was collected a total of 16528 individuals of soil macrofauna distributed in 20 orders and 119 mesofauna individuals, distributed in 6 order. The area had no grazing goats had the highest number of macrofauna individuals, with 5993 and mesofauna with 44 individuals. The most common and abundant macrofauna orders groups were Hymenoptera, Coleoptera, Araneae and Scutigeromorpha, and mesofauna: Acarina, Psocoptera and Collembola. The greatest orders richness, diversity and uniformity were found in the area II for macrofauna. The mesofauna showed greater orders richness and diversity in the area III and greater uniformity in the area I. The soil fauna diversity and evenness can be used as an environmental bio-indicator auxiliary of quality in Caatinga areas under goat grazing.